Enhancing Science Literacy and Critical Thinking Through Project-Based Chemistry Labs with Natural Materials - Ni Pt. Pande Mirah Surya Dewi; Yogo Dwi Prasetyo; Muhammad Syifa Ulkulbi; Syifa Dhiya Atun Nahri (Journal of Educational Chemistry (JEC), 2025)
The present study by investigating an alternative approach integrating natural materials to create more contextual and meaningful learning experiences. A quasi-experimental design was employed, with the experimental group engaging in hands-on laboratory projects using natural indicators such as purple cabbage extract, eggshell waste, and vinegar, while the control group received conventional instruction. Independent t-test analysis revealed a significant difference between the groups, with the experimental group outperforming the control group in post-test assessments of scientific literacy and critical thinking. These findings indicate that incorporating environmentally friendly, context-based materials into chemistry education could effectively enhance essential skills. Moreover, the project-based approach encouraged students to apply scientific concepts, think critically, and relate their learning directly to everyday life.